Evolución paleoambiental del Pleistoceno-Holoceno en el Valle de los Espejos - Carranza Rivera, Ana Gabriela (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
The Valley of the Mirrors forms the last remnant of what was the paleologist of and Acambay. It forms part of the central sector d of the Trans-Mexican Volcanic Belt (CVTM), located on the southern boundary of the Acambay d, occupying the northern portion of the Acambay-Tixmadejé fault. It is located in the mountainous area of ​​the municipality of Acambay, north of the state of M Mexico. The V Valle has a circular structure of more than 90 km2, whose plain shows that it was a lake, where the environmental paleo variability was recorded by recording the lake sediments of a core of 21.48 m Of the five longest nuclei that have been made in Mexico), through the analysis of paleo climatic indicators that include Organic Carbon (COT), Carbon Inorganic C (CIT), magnetic susceptibility, ICP-MS (Mass Spectrometry with Source of Inductive Coupling Plasma) and diatoms. The valley of the mirrors being or a closed basin, it is considered that its register includes until the last Iterglacial that corresponds to Late Pleistocene-Holocene, because it presented / displayed high sensitivity to paleoenvironmental changes registered in the sedimentary facies that are generally silty-loamy . The major elements along the whole core indicate that the source rock of contribution of the lacustrine sedimentation corresponds to volcanic materials of andesitic composition. Seven phases were identified in the sedimentary evolution based on the different proxies, two of them with high lacustrine level during the Pleistocene. The core base of 21.48 to 13 m, remained as a more unstable body of water with very constant increases in salinity, passing to conditions of Ciénega, which gradually deepens.

El valle de los Espejos conforma el último remanente de lo que fue el paleólogo de e Acambay. Forma parte e del sector central d del Cinturón Volcánico Transmexicano (CVTM), situado o en el límite sur del d graben n de Acambay, ocupando la porción septentrional de e la falla Acambay-Tixmadejé. Se localiza a en la zona montañosa del municipio de Acambay, al norte n del estado de M México. El V Valle presenta una estructura circular de más de 90 km2 , cuya planicie den nota de haber sido u un lago, donde se documentó la variabilidad v d paleo ambiental mediante el registro de e los sedimentos lacustres de un núcleo de 21.48 m (es s uno de los cinco núcleos más largos que e se han realizado en México), a través del análisis de indicadores paleo climáticos que incluyen Carbono Orgánico (COT), Carbono C In orgánico (CIT), susceptibilidad magnética, ICP-MS (Espectrometría de Masas con fuente de Plasma de Acoplamiento Inductivo) y diatomeas. El valle de los espejos siendo o una cuenca cerrada, se considera que su registro abarca hasta el Último Iterglacial que corresponde al Pleistoceno tardío-Holoceno, debido a que presentó alta sensibilidad a los cambios paleoambientales registrados en las facies sedimentarias que son generalmente limo-arcillosas. Los elementos mayores a lo largo del todo el núcleo indican que la roca madre fuente de aporte de la sedimentación lacustre corresponde a materiales volcánicos de composición andesítica. Se identificaron siete fases en la evolución sedimentaria en base a los distintos “proxies”, dos de e ellas con alto nivel lacustre durante el Pleistoceno. La base del núcleo de 21.48 a 13 m, se mantuvo como un cuerpo de agua más inestable con incrementos muy constantes en la salinidad, pasando a condiciones de Ciénega, que paulatinamente se profundiza.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Geociencias y Planificación del territorio
Keywords: info:eu-repo/classification/cti/1; IIMM-M-2013-0127; Evolución; Paleoambiental; Pleistoceno-holoceno; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5178